Relationship of serum ionized calcium and magnesium concentration with parasympathetic nerve Function in type 2 diabetes mellitus - Alam, Md Khairul; Begum, Noorzahan; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2016)
Background: Changes in serum Ca2+ and Mg2+ level may have some relationship to the occurrence of autonomic neuropathy in diabetes. Objective: To observe relationship between parasympathetic nerve function and serum ionized calcium & magnesium in type 2 diabetes mellitus (T2DM). Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka on 47 T2DM patients aged 40-68 years of both sexes. Twenty five patients were recently diagnosed diabetics (RDM) and 22 were long term diabetics (LDM) with 10-20 years duration of diabetes. Parasympathetic nerve functions of all patients were assessed by three simple non-invasive cardiovascular reflex tests. Ionized serum calcium and magnesium were measured by ion sensitive electrode method using NOVA electrode. Data were analyzed by unpairedttest and Pearsons correlation co-efficient test. Results: Serum ionized calcium and magnesium levels were significantly higher in RDM (P<0.001) and LDM (P<0.001) compared to healthy control. On correlation analysis, significant negative correlation of parasympathetic nerve function with Mg2+was found in both RDM and LDM patients. Conclusion: The result of this study concluded that higher calcium and magnesium ion may be associated with type 2 diabetes and parasympathetic nerve function of diabetic patients may have inverse relationship to serum Mg2+. Bangladesh Soc Physiol. 2016, December; 11(2): 70-73